Spatial dynamic modelling for urban scenario planning: A case study of Nanjing, China. (October 2020) - Cai, Zipan; Wang, Bo; Cong, Cong; Cvetkovic, Vladimir
Although urban scenario planning is widely applied for exploring various directions of urban development, it often has high requirements on the medium of quantitative information analysis and transformation. Thus, this study establishes a method of combining scenario planning with a spatial dynamic planning support system to predict urban growth. Specifically, a scenario-based spatial dynamic modelling method is integrated with the information module of planning policy for better decision support. The integrated modelling method is applied for an actual urban land use planning case of Nanjing, an evolving city in China. The spatial forms of future urban land use are simulated under four different pre-set policy scenarios. The differences in simulated results under multi-criteria restrictions reveal the effectiveness and practical value of the integration approach. The findings of this study provide policymakers with a process-based approach to test and evaluate 'what-if' consequences and help stakeholders reach consensus.